Informed consent for whole blood donation. Issue 1 (13th November 2019) - Grainger, Brian; Flanagan, Peter
Abstract : Background and objectives: It is recognized that blood transfusion services have an ethical duty to obtain informed consent from their voluntary, non‐remunerated donors. This right was most recently affirmed by the 2017 revision of the International Society of Blood Transfusion (ISBT) Code of Ethics. However, the constituent elements necessary to adequately inform such consent have not been definitively established. Materials and methods: This review evaluates the historical background to informed consent in medicine and as it has been applied to blood donation. The question of what information should be disclosed is then considered with regard to existing statutory requirements in both the United States and EU as well guidance from relevant international organizations. The emerging ethical issues around repurposing of donated blood for sale as recovered plasma and use in research are included in this analysis. Results: A reasonable basis is found in the literature to advocate that valid informed consent of blood donors should encompass: the donation process itself and potential adverse effects, the need for pre‐donation transfusion‐transmissible infection (TTI) screening, potential non‐transfusion uses of derived products, requirements to obtain and store personal information, the consequences that non‐disclosure of such information may have for both the donor and the recipient and reassurance as to the confidentiality of this information. Conclusion: Informed consent is a key component of the duty of care between a blood service and its donor. We identify essential elements that should be present for such consent to be considered valid.